DEHP deregulates adipokine levels and impairs fatty acid storage in human SGBS-adipocytes - Kristina Schaedlich (Nature Portfolio, 2018)
Abstract DEHP is a plasticizer which has been used in plastic products of everyday use for decades. Studies in mice and murine cell culture models identified DEHP as an endocrine disruptor that may also act as an obesogen. As this is of high concern in respect of the worldwide obesity epidemic, our aim is the translation of these findings into a human model system. On the basis of DOHaD, we investigated the influence of an environmentally relevant dose of DEHP [50 µg/ml] on adipogenesis in the human cell culture model SGBS. Pre-adipocytes were exposed to DEHP and differentiated into mature adipocytes. At different stages of differentiation, markers of adipogenesis like GLUT4, FABP4, LPL and PPARs, and of signaling pathways like AMPK/ACC2, JAK/STAT and MAPK were analyzed. Functional markers like adipokine secretion and triglyceride content as well as ROS production were measured in mature adipocytes. We found significantly lower expression levels of adipogenic markers, a reduction in lipid accumulation, higher leptin- and reduced adiponectin levels in the supernatant of treated adipocytes. Moreover, ROS production was significantly elevated after DEHP-exposure. In conclusion, DEHP led to lower grade of adipogenic differentiation in human SGBS-adipocytes under the chosen conditions.